The Virtual Supervision Revolution: Enhancing Counselor Competency in Tele-Mental Health Through AI-Enhanced Feedback Systems - Ranihusna, Desti (Yayasan Minang Darussalam, 2025)
The virtual supervision revolution has significantly transformed the way counselor competencies are developed, particularly in the context of tele-mental health services. This study explores the effectiveness of AI-enhanced feedback systems in improving professional skills during online supervision sessions. Using a qualitative research approach involving in-depth interviews and analysis of virtual supervision documentation, the findings reveal that AI integration enables faster, more objective, and structured feedback compared to traditional supervision methods. The system also facilitates enhanced self-reflection, ethical sensitivity, and data-driven decision-making among counselors. These outcomes suggest that AI technology holds great promise in fostering an adaptive, personalized, and sustainable training and supervision ecosystem in the digital era. Nonetheless, concerns related to data privacy, algorithmic accuracy, and technological infrastructure readiness remain critical issues that warrant further investigation.